2017
DOI: 10.1177/1932296817719290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structured Versus Unstructured Self-Monitoring of Blood Glucose on Glucose Control in Patients With Non-insulin-treated Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials

Abstract: In RCTs performed in non-insulin-treated patients with type 2 diabetes, SMBG is associated with a significant, although small, reduction in HbA1c. HbA1c reduction was greater with structured SMBG and when structured SMBG data were used to adjust diabetes therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 32 publications
5
52
0
10
Order By: Relevance
“…In a clinical trial with type 2 diabetes patients without insulin treatment, structured SMBG reduced the HbA 1c level by 0.32% . Mannucci E et al performed a meta‐analysis of the effect of structured SMBG on type 2 diabetes patients without insulin treatment and found that structured SMBG effectively reduced the HbA 1c level . However, no study has reported the sustained contribution of structured SMBG to diabetes self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical trial with type 2 diabetes patients without insulin treatment, structured SMBG reduced the HbA 1c level by 0.32% . Mannucci E et al performed a meta‐analysis of the effect of structured SMBG on type 2 diabetes patients without insulin treatment and found that structured SMBG effectively reduced the HbA 1c level . However, no study has reported the sustained contribution of structured SMBG to diabetes self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…patients without insulin treatment and found that structured SMBG effectively reduced the HbA 1c level. 13 However, no study has reported the sustained contribution of structured SMBG to diabetes self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experts from UK requested once daily testing at different times of the day, while Lu et al recommended performing at least two preprandial SMBG per day, and Bonomo et al and Chidum et al suggested distributing three tests through the week. A recent systematic review highlighted the benefits of structured SMBG over unstructured SMBG on glucose control in patients with non‐insulin‐treated T2D . However, the timing and frequencies of performing SMBG in the three RCTs included in this systematic review were also inconsistent.…”
Section: Introductionmentioning
confidence: 98%
“…A recent systematic review highlighted the benefits of structured SMBG over unstructured SMBG on glucose control in patients with noninsulin-treated T2D. 22 However, the timing and frequencies of performing SMBG in the three RCTs included in this systematic review were also inconsistent.…”
mentioning
confidence: 99%
“…It is recognized that self-monitoring of blood glucose (SMBG) helps to improve glycaemic control and identify hypoglycaemia in people with Type 1 and Type 2 diabetes treated with insulin, whilst there is ongoing debate regarding the clinical benefits of using SMBG in those with Type 2 diabetes who are not on insulin therapy [1]. Many studies and meta-analyses have been conducted since the first evaluation of SMBG in 1983 [2], with little consensus on the benefit, in part because of the variation in intervention regimens and study populations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In 2009, the International Diabetes Federation guidelines on SMBG use in non-insulin-treated Type 2 diabetes presented evidence supporting structured blood glucose (BG) monitoring combined with appropriate action [19].…”
Section: Introductionmentioning
confidence: 99%